Isolated optic nerve sarcoidosis - Suresh, Sandip; Kosmorsky, Gregory S; Lee, Michael S (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Objective: To report three cases of sarcoidosis confined to the optic nerve.Methods: Chart review of clinical, laboratory, imaging, and optic nerve biopsy findings and a review of the literature.Results: All three cases presented with progressive visual loss and showed enhancement of the intraorbital optic nerve on magnetic resonance imaging. There was no evidence for systemic disease, including a negative workup for sarcoidosis or other infiltrative pathologies. Optic nerve biopsy in each case showed non-caseating granulomas consistent with sarcoidosis.Conclusions: Sarcoidosis confined to the optic nerve is a rare phenomenon but should still be considered in the differential diagnosis of progressive optic neuropathy, even in the absence of systemic disease.